Advanced Simultaneous Isolation, Culture, and Identification of Myoblasts and Fibroblasts From Sternocleidomastoid Muscle of Congenital Muscular Torticollis. Issue 8 (November 2020) - Qiu, Xin; Zeng, Shuaidan; Xiong, Zhu; Tang, Shengping; Tang, Gen; Li, Shicheng
Abstract : Background: Congenital muscular torticollis (CMT) is a common pediatric disease caused by contracture of sternocleidomastoid muscle (SCM) that leads to neck stiffness and deformity. Based on the adhesion characteristics of different cells in affected SCM of CMT, myoblasts and fibroblasts can be isolated simultaneously by advanced culture conditions. Our study aimed to explore and optimize the isolation, culture, and identification of myoblasts and fibroblasts in SCM of CMT. Methods: Myoblasts and fibroblasts were separated by combined digestion with trypsin and collagenase. With this improved method, the morphology of isolated myoblasts and fibroblasts was observed under the microscope, the cell growth curve was drawn, and the purity of myoblasts and fibroblasts was determined by immunofluorescence. Results: The method allowed to satisfactorily culture myoblasts and fibroblasts. The cells could stably grow and be passaged, provided they were at least 80% confluent. Immunofluorescence of myoblasts and fibroblasts showed high rate of positive staining, and cell count showed excellent growth state. Moreover, according to the growth curve, fibroblasts grew at a higher rate than myoblasts. Conclusions: The isolated myoblasts and fibroblasts have high purity, intact structure, and relatively high vitality. This method can be used to establish a cell model with myoblasts and fibroblasts, which can be applied to investigate etiology of CMT or mechanisms of drug action. Abstract : Supplemental Digital Content is available in the text